Characterization of Vernaccia Nera (Vitis vinifera L.) Grape and Wine - Fracassetti, Daniela; Gabrielli, Mario; Corona, Onofrio; Tirelli, Antonio (South African Journal of Enology and Viticulture, 2017)
Vernaccia Nera (VN) is a minor Italian red grape cultivar whose oenological properties have not been investigated, yet. The traditional winemaking procedures with VN may include grape drying and even triple sequential fermentations, but a rational vinification approach should be based on the grape composition. Since a comprehensive characterization of VN grape is still missing, the ripening of VN grape was monitored by evaluating flavour compounds, proanthocyanidins and anthocyanins. The grapes were used to produce red wine whose chemical composition and sensory properties were assessed. Ripe VN grape contained high amounts of extractable anthocyanins (875 mg/kg). The most abundant anthocyanin was malvidin (56.6%) and high relative amounts of cumarate forms (11.3%) were also found. The grape skin showed high concentration of proanthocyanidins (2 g/kg) whose degree of polymerization was low (10.3). Epigallocatechin accounted up to 39% of the flavan-3-ol units in the skin. Flavour compounds in grape included glycosylated norisoprenoids (mainly 3-oxo-?-ionol and vomifoliolo) and benzenoids. The VN red wine showed high amount of anthocyanins, but the level of proanthocyanidins (0.93 g/L) was lower than expected. The spicy flavors were the notes mostly recognized with the sensory. Our data highlight VN grape is suitable for the production of ready-to-drink or shortly aged red wine due to the high acidity and low astringency.